Prevalence of Preschoolers Meeting vs Exceeding Screen Time Guidelines - Madigan, Sheri (JAMA Pediatr, 2019)
This study examines the prevalence of Canadian children ages 2 and 3 years meeting vs exceeding screen time guidelines and the strongest individual and family-level factors associated with failing to meet these guidelines.